Clinical and functional state of the retina after inadequate laser coagulation of peripheral vitreochorioretinal dystrophies. Part 1. Electroretinography - V. V. Neroev; G. Yu. Zakharova; I. V. Tsapenko; M. V. Zueva; T. D. Okhotsimskaya; B. M. Magamadov (Российский офтальмологический журнал, 2020)
Purpose of our work was to evaluate the effect of inadequate laser coagulation (LC) of peripheral vitreochorioretinal dystrophy (PVCRD) on the clinical and functional state of the retina. Material and methods. Ganzfeld ERG and multifocal ERG (mfERG) were recorded in 18 patients (32 eyes) with PVСRD in which, upon examination of the fundus, signs of inadequate retinal LC were detected and documented, such as hypercoagulation, an excessively large number of coagulates with minimal changes in the retina, or massive LC at the normal fundus. Results. The functional activity of the macular region after massive LC at the periphery of the retina in patients with PVCRD was shown to be reduced. The characteristic signs of reduction of the ganzfeld ERG and mfERG associated with a large volume of LC of the retina in patients without a history of surgical treatment of rhegmatogenous retinal detachment are described. For the first time, a functional method has been proposed to identify the risk of development and progression of macular dysfunction associated with massive LC of the retina, which includes a decrease in the amplitude of the waves of the maximal ERG and / or oscillatory potentials by 30 % or more with a parallel decrease in the density P1 in 1–3 rings of mfERG by 30 % and more as compared to the norm. Conclusion. Electrophysiological markers of macular dysfunction development risk associated with massive LC of the retina are proposed. The use of these markers in the clinic is important for predicting the risk of pathological changes in the macular region involving a decrease in visual functions, the choice of treatment tactics, and expert assessment of the volume of retinal LC redundancy.